Identification of resistant sources against Fusarium wilt of safflower: Identification of resistant sources against Fusarium wilt of safflower - H N AIWALE; D R MURUMKAR; L N TAGAD (Journal of Oilseeds Research, 2023)
A field evaluation of 37 advanced generation breeding material and parental lines of safflower was carried out under wilt sick plot condition at Solapur, Tandur and IIOR, Hyderabad for identifying resistant sources against Fusarium wilt. Four genotypes viz., GMU-5032, GMU-4109, SAF-19-20, and SAF-19-09 were found resistant to Fusarium wilt at all three locations. These resistant sources can be used in breeding programme for development of a variety resistant to Fusarium wilt.